Analysis Of Medical And Health Worker Practice Licenses In Semarang City 2025 - Alfi Sekar; Vilda Ana Veria Setyawati; Eka Pratiwi Maharani (Dian Nuswantoro Semarang, 2026)
A Practice License is a mandatory requirement for medical personnel (doctors and dentists) and health workers (nurses, midwives, pharmaceutical personnel, public health workers, environmental health workers, nutrition workers, biomedical engineering personnel, physical therapy personnel, medical technicians) in carrying out health service practices in accordance with the provisions of laws and regulations. This study aims to describe the Practice Licenses of medical personnel and health workers throughout 2025. The method used is quantitative descriptive with a secondary data source in the form of a recapitulation of practice licenses obtained from the Semarang City Health Office. The data was analyzed by presenting in the form of a table based on the profession group and the time of submission. The results showed that practice licenses involved various professional groups with varying numbers, where health workers and nurses were the professional group with the highest number. These findings show that the mechanism for licensing practice licenses has been widely used as a form of fulfilling the legality obligations of health workers' practice. This practice license data is expected to be the basis for evaluation in strengthening the licensing system and supervision of the practice of health workers in Semarang City.